Bacillus Calmette-Guerin Injections for Melanoma Immunotherapy. (April 2015) - Sogge, Steven M.; Fotos, Joseph S.; Tulchinsky, Mark
<x xml:space="preserve">Abstract</x> Abstract An 82-year-old woman presented for routine follow-up PET/CT after undergoing local melanoma resection in the left lower leg, isolated limb infusion chemotherapy, and immunomodulation therapy with Bacillus Calmette-Guérin (BCG) vaccine. Symmetric, bilateral, moderately intense FDG avid axillary and inguinal cutaneous nodules were observed that were new from the prior PET-CT. The patient had developed skin lesions at the BCG injection sites several months before the study. The case raises awareness to PET/CT appearance of local inflammatory response to BCG injection, which could be mistaken by an unaware reader for recurrent melanoma.